Penerapan Collaborative Learning Berbasis Ethnomatika Pola Bagas Godang Tapsel Untuk Meningkatkan Kemampuan Kreativitas Siswa Kelas VII-I - Fitria Jelita; Nurdalilah; Adek Nila Sari Harahap; Susi Silastri Lubis (JURNAL CERMATIKA, 2025)
The research method used was Classroom Action Research (CAR) conducted in two cycles during the second semester with the topic Quadrilaterals, applying the Collaborative Learning model based on Ethnomathematics of the Bagas Godang Pattern of South Tapanuli. This study aimed to determine: (1) the improvement of students’ creativity, (2) the enhancement of students’ learning activity, and (3) the improvement of teachers’ ability in applying the model. The research subjects were Grade VII-1 students of SMP Negeri 5 Padangsidimpuan in the 2024/2025 academic year. The results showed an increase in students’ creativity from 70% (“Fair” category) in cycle I to 86.67% (“Good” category) in cycle II. Students’ learning activity also improved from 67.42% (“Fair”) to 83.91% (“Good”). Teachers’ performance in implementing the model increased from 3.50 to 3.68 (“Good” category). These findings prove the effectiveness of the model in improving the quality of mathematics learning.